2017
DOI: 10.1002/ijc.30642
|View full text |Cite
|
Sign up to set email alerts
|

Dairy intake in relation to prostate cancer survival

Abstract: Dairy intake has been associated with increased risk of advanced prostate cancer. Two US cohort studies reported increased prostate cancer-specific mortality with increased high-fat milk intake. We examined whether dairy and related nutrient intake were associated with prostate cancer progression in a Swedish patient population with high dairy consumption. We prospectively followed 525 men with newly diagnosed prostate cancer (diagnosed 1989-1994). We identified and confirmed deaths through February 2011 (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Our study reflects the results of Pettersson et al and Downer et al and takes the next step to identify a particularly susceptible subgroup. We observed a statistically significant interaction between whole milk consumption and BMI.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study reflects the results of Pettersson et al and Downer et al and takes the next step to identify a particularly susceptible subgroup. We observed a statistically significant interaction between whole milk consumption and BMI.…”
Section: Discussionsupporting
confidence: 88%
“…Limited reported consumption of whole milk in the study population prevented the investigators from examining whole milk consumption and prostate cancer‐related death. Recent findings from Downer et al in a Swedish cohort found that men with localized prostate cancer who had the greatest high‐fat milk intake (≥3 servings/day) had a 6.1‐fold increased risk of prostate cancer‐related mortality relative to men consuming <1 serving/day (HR: 6.10; 95%CI: 2.14, 17.37; P ‐trend = 0.004). When men with advanced prostate cancer were included, increased high‐fat milk intake (≥4.5 servings/day) did not result in a significantly increased risk of prostate cancer‐related mortality relative to men consuming <1 serving per day (HR: 1.20; 95%CI: 0.69, 2.09; P < 0.09) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, I have recently read with interest the article entitled "Dairy intake in relation to prostate cancer survival." by Downer et al 1 that examined the effect of dairy nutrient intake on prostate cancer progression in 525 patients with high dairy consumption. The authors confirmed 222 deaths with prostate cancer-specific and 268 deaths by other causes.…”
mentioning
confidence: 99%
“…Lifestyle factors, such as a high‐fat diet (HFD), have been shown to play a crucial role in increasing the risk of different cancer types, and a number of clinical studies have linked HFD with several advanced cancers. A study on a large cohort of European women linked a diet rich in saturated fat to increased risk of developing estrogen‐ and progesterone‐receptor‐positive breast cancer (Sieri et al , ), while progression of localized prostate cancer was promoted by an intake of high‐fat dairy produce, with increased cancer‐related mortality (Downer et al , ). Preclinical studies also provide support for the hypothesis linking HFD to cancer progression.…”
mentioning
confidence: 99%